Effects of Environmental Strategy, Uncertainty and Top Management Commitment on the Environmental Performance: Role of Environmental Management Accounting and Environmental Management Control System - Appiah, Bismark Kusi; Donghui, Zhang; Majumder, Shapan Chandra; Monaheng, Malepekola Precious (International Journal of Energy Economics and Policy, 2019)
The aim of this paper is to check the effect of top management commitment, perceived environmental uncertainty and environmental strategy on the environmental performance of manufacturing firms of China by considering the role of EMA and EMCS. With the increase in economic activities the environmental issues have also increased. Companies are now more conscious for the preservation of environment and thus are working on it. Environmental Accounting is the system through which companies manage environmental issues. Economic development of any country along with the well-being of that country’s society can only be attained when there is equilibrium between optimization of wealth and environmental protection. This perspective is raising its importance day by day and hence spreading awareness in public and government as well. Therefore, there is more pressure on companies to focus on environmental protection and to align their operations in such a way that there is no damage to the ecosystem. On the basis of results of this research it is believed that EMA and EMCS play very important role in the achievement of perfect environmental performance. EMA and EMCS are two separate tools and good mediators which improve the performance of the firm regarding environment and align the management regarding environmental costs with sequence. This study will help government and manufacturing firms in making policies regarding environment friendliness through environmental management accounting and environmental management control system as previous studies have also generated same kind of help and benefits. Keywords: China, Environmental strategy, Environmental Management Control System, Environmental Management Accounting JEL Classifications: Q56, Q58 DOI: https://doi.org/10.32479/ijeep.8697